High Expression of COX-2 Associated with the Depth of Invasion on Acral Melanoma by Increasing TGF-β1 - Gipsyianti N; Aziz A; Hernowo BS; Usman HA (Dove Medical Press, 2021)
Nastassa Gipsyianti, Afiati Aziz, Bethy S Hernowo, Hermin A Usman Department of Pathology Anatomy, Faculty of Medicine, Universitas Padjadjaran/Dr. Hasan Sadikin General Hospital, Bandung, IndonesiaCorrespondence: Hermin A UsmanDepartment of Pathology Anatomy, Faculty of Medicine, Universitas Padjadjaran/Dr. Hasan Sadikin General Hospital, Bandung, IndonesiaEmail hermin.seroja@gmail.comIntroduction: Acral melanoma (AM) has a poor prognosis since it is easily metastatic and resistant to chemo and immunotherapy. Cyclooxygenase-2 (COX-2) is an enzyme that plays a role in the carcinogenesis process. The increased expression of COX-2 has an impact on increasing levels of Myeloid-Derived Suppressor Cell (MDSC), which is a key regulator of immune. The increase in MDSC produces Transforming Growth Factor β 1 (TGF-β 1), which will suppress Natural Killer (NK) cells and Dendritic Cells (DC) function so that tumor cells are spared from the immune systems and are easier to invade surrounding tissues.Purpose: This study aimed to determine the role of COX-2 and TGF-β 1 on the depth of invasion on AM.Materials and Methods: This study was a cross-sectional observational study on 40 paraffin blocks of AM cases during 2014– 2019 in the Department of Pathology Anatomy, Faculty of Medicine, Dr. Hasan Sadikin General Hospital, Bandung. The depth of invasion of all samples was measured by dotSlide imaging software and the immunohistochemical staining of COX-2 and TGF-β 1 was performed. The association between COX-2 and TGF-β 1 expression and AM depth of invasion were analyzed using Mann Whitney.Results: The result showed a significant association between COX-2 and TGF-β 1 expression and depth of invasion on AM. COX-2 expression had a significant association with TGF-β 1 expression (0.0001). Through multivariate analysis, it was found that COX-2 had the greatest association with the depth of invasion (p=0.0001).Conclusion: The findings showed that increasing expression of COX-2 in AM is associated with the depth of invasion by increasing TGF-β 1 and it might play important roles during the invasion process of AM.Keywords: acral melanoma, COX-2, depth of invasion, TGF-β 1